The Algorithmic Athlete: What is the Future of AI in Sports Medicine? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The world of high-performance athletics has always been a crucible for human potential, but its future is increasingly being shaped by the convergence of bio...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics